The study of relationship between Maternal Reactions to Children’s Negative Emotions and Children’s Social Skills The role of mediational Emotion Regulation - Khabir, Leila; Farid Ghasrodashti, Marzieh; Rahimi, Changiz (International Journal of Applied Behavioral Sciences, 2015)
Introduction: Differences in emotional control and social skills appear to partially reflect differences in longstanding intrapersonal qualities, such as temperament, but parenting characteristics also have emerged as indicators of how children develop emotional and social competence. Methods: The study design was correlational. Sample was 60 children in age preschool (30 boys and 30 girls) and their mothers (60 females) selected using convenience sampling among children were registered for preschool in a private school. Instruments were used in this study include: Coping with Children’s Negative Emotions Scale (CCNES), Behaviour Rating Inventory of Executive Functioning (BRIEF), Social Skills Rating System (SSRS). Data analyzed using simple regression and structural equation modeling (SEM). Results: Data analysis showed that children’s emotion regulation skills predicted their social skill levels (F=69.98, p=0.0001) and Total maternal emotion socialization predicted children’s emotion regulation (F=98.15, p=0.0001) and children’s social skills (F=39.45, p=0.0001). Other result was children’s emotion regulation skills completely mediated relation between reactions to children’s negative emotions and children’s social skills. Conclusions: This research highlighted the important impact of emotion-related parenting behaviours and beliefs on children’s development of social and emotional competence.